95 Specific Recognition of the Major Birch Pollen Allergen BET V 1 Programs Dendritic Cells to Induce Either th2 or Tolerogenic Responses - Smole, Ursula (World Allergy Organization Journal, 2012)
BACKGROUND: Only a limited number of proteins have the potential to induce Th2-polarized immune responses and specific IgE in genetically predisposed individuals. However, why the contact with an allergen results either in allergic sensitization or tolerance induction has remained unclear so far. Here, we focused on the in depth study of uptake, induction of signal transduction pathways, and gene regulation in monocyte-derived dendritic cells (MoDCs) of allergic and normal individuals in response to the major birch pollen (BP) allergen Bet v 1.0101 and its structural homolog from celery, Api g 1.0101. METHODS: Live cell fluorescence microscopy was used to analyze uptake kinetics, competitive binding, and internalization pathways of labeled allergens by iMoDCs. To delineate allergen-mediated gene activation, iMoDCs were incubated with the allergens, a control stimulus, or left untreated followed by real-time PCR-based gene expression profiling. Surface-bound IgE was detected by immunofluorescence microscopy and IgE-mediated gene activation by real-time PCR. RESULTS: Comparable kinetics of Bet v 1.0101 and Api g 1.0101 uptake were observed for both allergic and healthy donors. In competititve binding assays, however, Bet v 1.0101 outcompeted Api g 1.0101 for surface recognition in both donor groups. Pharmacological inhibition evidenced that Bet v 1.0101 internalization occurred in a receptor-mediated manner showing characteristics of lipid raft-dependent endocytosis. MoDCs of both donor groups were IgE positive and showed marked upregulation in NF-κB dependent genes after Fcε receptor activation by anti-IgE. Bet v 1.0101-stimulation, in contrast, exclusively triggered transcription of the Th2 cytokines IL-4 and IL-13 but not NF-κB related genes in MoDCs of BP allergic donors. Healthy donors were either unresponsive or showed elevated mRNA levels of the Th1-promoting chemokines CXCL10 and CXCL11. CONCLUSIONS: This study supported by grant SFB-F1802 of the Austrian Science Fund shows for the first time that the allergen uptake is specific and similar in DCs from allergic and healthy individuals. More important, the ensuing signal cascade that is triggered by the allergen differs between DCs of the 2 donor groups and results in a Th2-polarized immune response in allergic individuals as compared to ignorance/tolerance in normal donor cells.